Condutividade hidráulica após ensaio de squeezing de GCL percolado com água - Luvison, Camila Miotto da Silva (2022)
The use of bentonite geocomposites (GCL) has proven to be an efficient alternative for barriers system in landfill works, with the function of protecting the soil and groundwater from contamination. This material presents low hydraulic conductivity when hydrated, increasing its thickness due to the expansion of bentonite, which, however, makes it more fragile. This expansion exposes the GCL to the possibility of the occurrence of the phenomenon known as lateral displacement of bentonite (squeezing). This phenomenon is a consequence of a stationary, non-perforating load applied to the GCL, which is installed under insufficient topsoil, and may result in an increase in the permeability of the material. In this context, the objective of this research was to study the hydraulic conductivity of GCL permeated with water, after the phenomenon of lateral displacement of bentonite (squeezing). To achieve this goal, samples (GCL + topsoil) were subjected to static loading through a CBR (California Bearing Ratio) piston, in modified version, with ratios H/B (H is the thickness of the topsoil and B the diameter of the piston) of 1.0;1.5;2.0, in triplicate. Next, the samples were submitted to hydraulic conductivity testing, in triplicate, in a flexible wall permeameter. All samples showed high values of permeability (around 10-9 m/s) at the beginning of percolation, followed by a gradual reduction until they reached a characteristic value of approximately 5 x 10-11 m/s. The samples with H/B = 1.0 presented the squeezing phenomenon, however, by the end of the hydraulic conductivity test they had regenerated, thus demonstrating that the GCL can guarantee an adequate functioning, even when there is lateral displacement of the bentonite.